Metal-free C–H arylation of aminoheterocycles with arylhydrazines. Issue 27 (7th July 2016) - Taniguchi, Toshihide; Imoto, Mitsutaka; Takeda, Motonori; Matsumoto, Fukashi; Nakai, Takeo; Mihara, Masatoshi; Mizuno, Takumi; Nomoto, Akihiro; Ogawa, Akiya
Abstract: A direct C–H arylation of aminoheterocycles with arylhydrazine hydrochlorides was developed. The reaction proceeds via a homolytic aromatic substitution mechanism involving aryl radicals as the intermediates. The new reaction takes place readily at room temperature in air and in the presence of an inexpensive base. Moreover, the reactivity of this radical arylation correlated with the HOMO energy of aminoheterocycles. This method provides not only a rapid access to diverse arylated heterocycles, but also an atom-efficient alternative to conventional transition-metal-catalyzed cross-coupling between halides and organometallics. Graphical abstract: